Faecal Parasitology: Concentration Methodology Needs to be Better Standardised. - Monika M Manser; Agatha Christie Santos Saez; Peter L Chiodini (Public Library of Science (PLoS), 2016)
To determine whether variation in the preservative, pore size of the sieve, solvent, centrifugal force and centrifugation time used in the Ridley-Allen Concentration method for examining faecal specimens for parasite stages had any effect on their recovery in faecal specimens.A questionnaire was sent to all participants in the UK NEQAS Faecal Parasitology Scheme. The recovery of parasite stages was compared using formalin diluted in water or formalin diluted in saline as the fixative, 3 different pore sizes of sieve, ether or ethyl acetate as a solvent, 7 different centrifugal forces and 6 different centrifugation times according to the methods described by participants completing the questionnaire.The number of parasite stages recovered was higher when formalin diluted in water was used as fixative, a smaller pore size of sieve was used, ethyl acetate along with Triton X 100 was used as a solvent and a centrifugal force of 3,000 rpm for 3 minutes were employed.This study showed that differences in methodology at various stages of the concentration process affect the recovery of parasites from a faecal specimen and parasites present in small numbers could be missed if the recommended methodology is not followed.